Comparative adaptability of 307 Saccharomyces cerevisiae strains from winemaking and Mantou fermentation - Su, Cairong; Wang, Hui; Jia, Yiming; Wang, Wenhua; Ma, Xueli; Han, Peijie; Zhu, Lixia (Frontiers in Microbiology, 2025)
Domesticated Saccharomyces cerevisiae is one of the most significant microbial populations in human civilization due to its remarkable diversity and high adaptability to human environments. However, the adaptability mechanisms underlying this population ecological behavior remain unclear. This study explored the adaptive behaviors of S. cerevisiae strains from the Wine and Mantou genetic lineages under both artificial stress conditions and natural or near-natural environments. A total of 307 diploid S. cerevisiae strains were analyzed, including 169 strains derived from grape sources and 138 from sourdough sources. Various stress factors, including sodium chloride, tannins, ethanol, pH, temperature, and sulfur dioxide (SO2), as well as different substrates (natural grape juice, simulated grape juice, and simulated dough), were applied to evaluate adaptability. The results demonstrated that Wine population exhibited superior performance in grape juice environments, characterized by higher CO2 production. The biomass of both the Wine and Mantou populations in the simulated dough was significantly higher than that in the simulated grape juice. In the simulated grape juice environment, the adaptability of the Wine population was significantly superior to that of the Mantou population. In contrast, in the simulated dough environment, the Mantou population exhibited better adaptability than the Wine population. Furthermore, Wine population displayed higher tolerance to ethanol, extreme temperatures, tannins, and sodium chloride in YPD medium compared to Mantou population. Diploid strains also exhibited greater stress tolerance than haploid strains. These findings offer valuable insights into the distinct adaptive mechanisms of domesticated S. cerevisiae lineages.